Pemberdayaan Masyarakat Kelurahan Tenggilis Mejoyo Melalui Sosialisasi DBD dan Pelatihan Semprotan Nyamuk Alami dari Tanaman Serai - Kania Luthfiyyah; Ajeng Dwi Larasati; Fadli Zikri Arvinsyah; Muizzul Rizqon Gunawan; Dwi Wahyuningtyas (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The high incidence of Dengue Hemorrhagic Fever (DHF) in Tenggilis Mejoyo Urban Village, Surabaya City, along with the community's dependence on chemical-based mosquito repellents, serves as the primary background for this community service activity. The objective of this program is to empower the community, particularly the women of Kader Surabaya Hebat (KSH), through education on DHF prevention and training in the production of a natural mosquito spray from lemongrass (Cymbopogon nardus) as a safe, environmentally friendly, and economically potential alternative. The implementation method involved a participatory socialization approach in collaboration with the local Public Health Center (Puskesmas) and a direct demonstration of the product-making process. The results showed a very positive response and high enthusiasm from the participants. There was an increased community awareness regarding the use of natural ingredients for disease prevention, and the participants successfully acquired the technical skills to produce the mosquito spray independently. Furthermore, a significant creative economy potential was identified, where the product can be produced at a low cost and sold at an affordable price to the wider community. In conclusion, this empowerment program successfully integrated a preventive health solution with entrepreneurial potential, creating a model of community self-reliance in facing the challenge of DHF while simultaneously opening new economic opportunities at the community level.